Ab initio informed yield criterion across body-centered cubic transition metals. (1st September 2022) - Bienvenu, Baptiste; Dezerald, Lucile; Rodney, David; Clouet, Emmanuel
Graphical abstract: Abstract: Plasticity of body-centered cubic (bcc) metals is atypical at low temperatures, caused by the important lattice friction of 1 / 2 〈 111 〉 screw dislocations. In this paper, we present a yield criterion that can be used to predict yield stress and active slip systems in all bcc transition metals for any applied stress. The criterion is fully parametrized on ab initio calculations of 1 / 2 〈 111 〉 screw dislocation glide properties, and is applied in the case of uniaxial loading to compare with tension and compression experiments at low temperature. The criterion describes most of the different plastic behaviors observed experimentally in different metals, i.e. the dependence of the yield stress and active slip system on the orientation of the loading axis, as well as the tension/compression asymmetry. We find that plastic yield generally occurs at lower stresses in tension than in compression but for some metals, in particular niobium, there are large regions of the stereographic projection where compression is easier.